Feature extraction and classification algorithms for assessing muscle condition using multi sensors - Mohamed Sarillee, Mohamed @ Mohd Kassin (Universiti Malaysia Perlis (UniMAP), 2017)
Master of Science in Biomedical Electronic Engineering